Transition of Laboratory Management System Based on ISO/IEC 17025:2017 at SNSU-BSN - Chery Chaen Putri; Melati Azizka Fajria; Adindra Vickar Ega; Eka Pratiwi; Yulita Ika Pawestri; Nelfyenny Nelfyenny; Muhammad Haekal Habibie (LIPI Press, Anggota IKAPI, 2021)
To accommodate current technological developments and laboratory conditions, ISO (International Organization for Standardization) and IEC (International Electrotechnical Commission) published the latest version of the ISO/IEC 17025 standard in 2017. Complying with ISO/IEC 17025:2017 enables laboratory to provide measurement results that are valid and traceable to international unit system. SNSU-BSN as National Metrology Institute (NMI) in Indonesia has transformed its management system from the old version ISO/IEC17025:2005 to the current ISO/IEC 17025:2017 in 2019. This study explains the process of SNSU-BSN transition in order to establish a management system complying with ISO/IEC 17025:2017. A comparison between the implementation of the old and the current ISO/IEC 17025 was explained along with its impacts and benefits. This study shows that SNSU-BSN as a NMI in Indonesia has successfully implemented the full implementation of the transition from ISO/IEC 17025:2005 to ISO/IEC 17025:2017 in accordance with the time-frame determined by the Joint ILAC-ISO and KAN.